About building virtual worlds. Experience in teaching an interfacultural course at Lomonosov Moscow State University - A. Segal P.; A. Savchenko V.; A. Kostikova A.; А. Сегал П.; А. Савченко В.; А. Костикова А. (Professional education in the modern world, 2021)
Subject of the article is actual as never given the speed and volatility of data transfer and it’s processing. Authors have attended the topic of “digital transformation” multiple times, researching both negative and positive outcomes of this process. To define some of the potentially negative - alienation from other elements of life due to division of labor, personal and professional diviations. Some of the standing out positives - RnD and creative potential provided by virtual space, ability to effectively model technical and social processes, gamification as an additional tool of education development. This article is focused around the methodology of the elective education course “Constructing virtual worlds: game, science fiction and futurology” that was held in 2020/2021. Authors provide detailed description of how this course has been formed and method of its delivery to the audience. Being done as the dialogue between speakers and students, through the means of constant discussion, the course allowed not just to constantly receive and apply feedback to real-time, but also to form a thought process, reasonable for subjects in discussion. The course has provoked a lot of interest both in academic and industrial circles and has been discussed at multiple professional media platforms. Major results are ability to develop disciplines for new masters programs and programs of additional specialization. Authors are also confident that the course can be the beginning of new research and practical transdisciplinary fields aimed to explore vision and ideas of virtual space, cyber space and metaverse. Актуальность статьи определяется бурным развитием процессов передачи и обработки информации. Авторы уже неоднократно обращались к теме так называемой «цифровой трансформации», рассматривая как негативные, так и позитивные последствия этих процессов. К первым можно отнести выделение этой области в отдельную сферу деятельности, ее неизбежное отчуждение от других сфер в силу разделения труда, профессиональные и ...